(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The purpose of this study was to investigate the extent to which medium and small manufacturing enterprises in India had embraced digitization. The purpose of this study is to determine what variables, such as firm size, adoption motives, and adoption barriers, impact the adoption of digitalization. Descriptive statistics, logistic regression, and t-tests were used for data evaluation. The study found that the size of the firm had a major impact on how often digitalization was used. Sales, profitability, competitiveness, and brand awareness all saw increases that were most closely linked to the adoption of digitalization. Organizations faced several challenges on the road to digitization; the most important of them were users’ dissatisfaction with the current system, high prices, a lack of appropriate technology, and support from higher management. According to the survey, there are several benefits to embracing digitization, therefore companies who haven’t done so yet should think about it.